Towards Cooperative Patient Management Through Organizational and Medical Ontologies - Falasconi, S.; Dazzi, L.; Lanzola, G.; Quaglini, S.; Saracco, R.; Stefanelli, M. (Methods of Information in Medicine, 1998)
Within knowledge and data engineering a new research paradigm is emerging based on the Multi-Agent System (MAS) architectural framework, allowing human and software agents to interoperate and thus cooperate within common application areas. In such a framework, knowledgeable agents of heterogeneous nature, that possess diverse but at least partially compatible or inter-translatable conceptual views, or ontologies, modeling both their own expertise and the external environment, make somehow available their information resources or problem-solving abilities for cooperative processes addressing the construction of a new agent or the achievement of some common goal through a correlated execution of tasks.In this paper, we restrict our analysis to the case of an organization of cognitive agents, illustrated with examples from a prototypical healthcare MAS, that is, a so-called Distributed Healthcare Information System (D-HIS). The prototype makes use of an ontological library written in the standard language Ontolingua. An ongoing application of the methodology to the main problem of Clinical Practice Guidelines (GLs) computer-based dissemination and enforcement is described.
Keywords: Agent; Ontology; Organization; Distributed Healthcare; Clinical Practice Guideline